Peningkatan Keterampilan Menyimak Dongeng Dengan Menggunakan Media Animasi Audiovisual Melalui Metode Think Pairs Share Pada Siswa - Gusmaidar Gusmaidar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
This study uses classroom action research design. Subjects of this study is the ability to listen to fairy tales class VII 7 SMP N 1 Nan Sabaris. This study is divided into pre-stage cycle, the first cycle and the second cycle. Techniques of data retrieval is done by using test questions, observations, interviews, journals, and photo documentation. Data analysis included quantitative and qualitative data. Quantitative data shows the results of tests listening fairytale, while quantitative data shows changes in student behavior. in the first cycle of 64.13, and the second cycle reaches 76.67. it showed an increase from the pre cycle to cycle II reached 13.8%. In detail, the average value of the aspect of finding intrinsic elements in fairy tales prasiklus stage was 18.2, the first cycle was 27.2, while in the second cycle reaches 32. In the aspect of finding interesting things from fairy tales, the average value of students in the first cycle was 37.8, and the second cycle of 45. Based on the results nontes, students also experience changes in behavior